Apraxia in Motor Alalia in Children - Dilnoza Jamilova (Scientific Trends, 2025)
Alalia is a speech disorder occurring with normal hearing and intelligence, developing against the background of organic brain damage before the age of three. Systemic underdevelopment of speech in alalia is characterized by disturbances in phonetic-phonemic and lexical-grammatical structures. Non-speech syndromes may also be noted in alalia: motor (movement and coordination disorders), sensory (sensitivity and perception disorders), and psychopathological. Alalia is classified into motor, sensory, and mixed types. In motor alalia, the formation of expressive speech is impaired, affecting speech praxis, articulation, and fluency, while the understanding of others' speech remains intact.
Keywords: Motor alalia, sensory alalia, speech development in children, apraxia.